2021
DOI: 10.3390/healthcare9121756
|View full text |Cite
|
Sign up to set email alerts
|

Confinement by COVID-19 and Degree of Mental Health of a Sample of Students of Health Sciences

Abstract: Background: In response to the global COVID-19 pandemic, most countries have taken important measures to control the spread of the virus, such as population confinement and the closure of universities. Objective: The main objective of this study is to evaluate how the situation resulting from COVID-19 has affected the mental health of a group of health sciences students. Material and Methods: This is a cross-sectional, descriptive, observational study with a sample of 160 people, conducted through an online su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…No entanto, o retorno às atividades práticas era necessário, em especial nos cursos de Odontologia. Existem relatos de acadêmicos dos cursos de Medicina e Enfermagem que foram afetados negativamente com a situação da pandemia, enfrentando dificuldades na adaptação da rotina e frustrações 4 .…”
Section: Introductionunclassified
“…No entanto, o retorno às atividades práticas era necessário, em especial nos cursos de Odontologia. Existem relatos de acadêmicos dos cursos de Medicina e Enfermagem que foram afetados negativamente com a situação da pandemia, enfrentando dificuldades na adaptação da rotina e frustrações 4 .…”
Section: Introductionunclassified
“…Reference [ 4 ] also mentioned the effects of lockdowns on psychology, the environment, and the economy. Various studies have shown the effects of lockdowns on economics, domestic abuse, mental health, and social health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%